Factors related to low social participation in older adults: findings from the Fibra study, Brazil - Juliana Martins Pinto; Anita Liberalesso Neri (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2017)
Abstract Objective To investigate the factors related to low social participation in older adults. Method A hierarchical model was drawn using data from 2,251 participants of the Fibra study, aged 65 years or more, without cognitive impairment suggestive of dementia, who were living in seven Brazilian cities. Three blocks of variables were considered: macrostructural, socioeconomic and health conditions. Results Factors related to low social participation were low perceived social support (OR:2.18;CI:0.73-1.53; <0.001), vision impairment (OR:2.04; CI:1.16-3.61;0.014), age over 80 years (OR:2.03;CI:1.22-3.38;0.006), depressive symptoms (OR:1.86;CI:1.29-2.68; <0.001), low cognitive status (OR:1.85;CI:1.20-2.85;0.005) and slowness (OR:1.83;CI:1.26-2.65;0.001). Older adults with those conditions have higher odds to be less socially engaged than their counterparts. Conclusion Personal conditions, such as socioeconomic and health status were predictors of low social participation in older adults. Initiatives aiming at active aging promotion should focus primarily on vulnerable elderly, especially those with health and/or social disadvantages.